Hubungan Petunjuk Prestasi Utama Fasiliti Masjid dan Tahap Kepuasan Pengguna Menerusi SERVQUAL di Terengganu - Siti Nur Zahirah Zawawi,; Mohd Hafizal Ishak, (Research in Management of Technology and Business, 2024)
The mosque located in Terengganu attracts attention from both domestic and international tourists with its unique architecture, accompanied by facilities that meet the needs of visitors. There are various types of mosques in Terengganu, including tourist mosques, state mosques, district mosques, and university mosques. This study was conducted to identify key performance indicators of mosque facilities and analyze the key performance indicators of mosque facility management with the satisfaction level of users through SERVQUAL elements. To achieve the research objectives, a quantitative method was applied through a survey conducted with 70 respondents, including the Islamic Religious Department of Terengganu, mosque committee members, and mosque users across the state. In this research, the researcher successfully identified key performance indicators of mosque facilities in Terengganu. The first research objective found that key performance indicators for space utilization have a high average value, while key performance indicators for the efficiency of implemented work have the lowest average value. The results of the second research objective found that key performance indicators for mosque management have a significantly high value. Therefore, the researcher concludes that key performance indicators of mosque facilities strongly influence the satisfaction level of mosque users in Terengganu.